1939
DOI: 10.1139/cjr39b-019
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Mechanism and Kinetics of the Sulphite Process

Abstract: The rate of delignification of resin extracted spruce wood-meal has been determined in calcium-base sulphite liquor at temperatures from 130 °C. down to 50 °C. No break was found in the temperature coefficient curve at the lower temperatures, the reaction following the Arrhenius equation closely. Possible mechanisms of the reaction are discussed in the light of existing theories, and the effect of temperature on the yield of pulp is pointed out for its practical interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

1941
1941
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…3) lends support to the peptizatioil theory of sulphonation proposed by Calhoun, Yorston, and Maass (22). The trends in Fig.…”
Section: Discussionsupporting
confidence: 66%
“…3) lends support to the peptizatioil theory of sulphonation proposed by Calhoun, Yorston, and Maass (22). The trends in Fig.…”
Section: Discussionsupporting
confidence: 66%
“…Dabei sei die Sulfonierung des Lignins die steuernde Reaktion und nicht die Hydrolyse der gebildeten Ligninsulfonsäure (95,96).…”
Section: Einfluß Des Reaktionsmittels Auf Die Komponenten Des Holzes unclassified
“…Corey and Maass (1936) cooked two samples of spruce wood meal at several temperatures and assuming a first-order relation showed that variation in reaction rate with temperature followed the Arrhenius equation between 212°a nd 284°F. Calhoun et al (1939) showed that the rate of pulping is a function of liquor concentration as well as lignin content. Goldfinger (1941) analyzed the data of Corey and Maass (1936) and Calhoun et al (1939) and indicated that there is a change in the order of reaction during the cook.…”
mentioning
confidence: 99%
“…Calhoun et al (1939) showed that the rate of pulping is a function of liquor concentration as well as lignin content. Goldfinger (1941) analyzed the data of Corey and Maass (1936) and Calhoun et al (1939) and indicated that there is a change in the order of reaction during the cook. Rawlings and Staidl (1925) were the first to study the effect of cooking aspen wood with a solution of sodium sulfite in the temperature range of 248°to 365°F.…”
mentioning
confidence: 99%